ARCHITECTURAL POLYGLOSSIA IN PUBLIC BUILDING FACADES OF LATE OTTOMAN PERIOD - Sener, Mehmet; Bayraktar, Neslihan Türkmenoğlu (Journal of Islamic Architecture, 2018)
The 19th century was a period of significant transformations in Ottoman architecture in terms of the professionalization of discipline and the actualization of new construction technologies and architectural styles. The basic reason for this situation was the changing politics of Ottoman rulers that was based on the aim of achieving westernization in every aspect of life. In this context, an architectural medium has occurred especially in public building constructions where western based design approaches dominated the architectural production. Whereas, public buildings having different architectural characteristics than this westernization based architectural production, were also constructed in different peripheries of the empire. It is argued in this article that public buildings with polyglossia architectures were built in those regions that were generally concentrated on the facades and had architectural qualities different than the public building constructions executed mostly in İstanbul and other central cities of the empire. In this framework, the characteristics of these polyglossia observed on public building facades that contributed to the formation of architectural diversities in the empire are aimed to be examined. These polyglossia approaches that didn’t transform into stabled architectural styles are evaluated within the framework of the design components and constructional elements applied on the buildings.